Kenya’s Education Policy versus Implementation: Implications on Wholesome Education for the Girl Child - Ouma , Jane N.; Indangasi , Henry; Ontita , Edward (African Journal of Education,Science and Technology (AJEST), 2021)
The ultimate goal of education is to train an individual to fit in and work in society. Therefore, the education policy of a country is supposed to give a hint on what the education of that particular country looks like. This is because the policy contains the guidelines of how the system of education is to be implemented. In Kenya, the education policy stipulates wholesome education for all. It is well formulated, setting very clear provisions on wholesome education for all. However, there is a distortion at the point of implementation, an overemphasis on academic rigour, particularly, in covering the subject syllabus and scoring high grades in examinations. This is done at the expense of quality and balanced learning. The necessity for wholesome education, as stated, is to prepare one for life, in response to challenges that face humanity and to impart the necessary skills, values and competencies that help develop productive, healthy and globally engaged citizens. Wholesome education is, therefore, preferred so that children can be as good at school as they are at home, where the latter represents the family and the community at large. While wholesome education is necessary for all, it is particularly critical for the girl child since they will become mothers and caregivers around whom the family coalesces. With wholesome education, the girl child will equally handle what is learnable at school as well as at home, thereby, leading them to be better people in society. However, the efficacy of the policy can only be weighed against the level and method of the policy implementation. This paper therefore attempts to interrogate Kenya’s education policy vis a vis its implementation. In particular, the paper purposes to investigate the implementation of Kenya’s education policy in relation to wholesome education for girl children.